Strategi Guru dalam Mengoptimalkan Media Visual untuk Pembelajaran Anak Tunarungu di Sekolah Dasar - Ahmad Farhan (Journal of Research in Education & Technology, 2025)
This study aims to analyze teachers’ strategies in optimizing the use of visual media in teaching deaf students at a public elementary school in Madura. Hearing impairments cause deaf students to experience barriers in verbal communication and in understanding instructional materials. his research employed a descriptive qualitative approach using observation and interview techniques. Data were analyzed thematically through the stages of data reduction, data display, and conclusion drawing, and were verified through source and methodological triangulation. The findings indicate that teachers utilize picture cards, instructional videos, visual schedules, and digital presentations as the primary means of delivering learning materials. Visual repetition strategies, the use of simple symbols, and contextual activities were found to strengthen students’ comprehension. The challenges encountered include limited access to supporting technology and insufficient special education training for teachers. Nevertheless, teachers demonstrated strong pedagogical adaptability and maintained collaborative communication with parents. This study concludes that structured visual-based instruction is effective in supporting inclusive education for deaf students.